The Effect of Topography on SCORE: an Investigation Based on Simulated Spaceborne Multichannel SAR Data - Bordoni, Federica; Rodriguez-Cassola, Marc; Prats, Pau; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2018)
Scan-on-Receive (SCORE) is an established Digital Beamforming technique for multichannel spaceborne Synthetic Aperture Radar (SAR) systems. Nevertheless, the effect of topographic variations on SCORE deserves further investigation, especially when SCORE involves the use of sharp elevation and/or wide azimuth beams, as in case of advanced operational modes. This paper investigates the effect of topography on the SAR image obtained by SCORE, in dependence of main SAR system parameters, by means of a simple end-to-end simulator based on real data acquired by the German satellite TerraSAR-X.
Keywords: Synthetic Aperture Radar (SAR); Scan-on-Receive SCORE; Digital Beamforming (DBF)